Development and Application of Targeted Multi-plex Polymerase Chain Reaction to Help Diagnose Infectious Uveitis - Ethelind, Rachel; Rina La Distia Nora (Majalah Oftalmologi Indonesia, 2025)
Introduction: Clinical pattern recognition is paramount in uveitis diagnosis. Pathogen detection from ocular fluid samples is often necessary to support infectious uveitis diagnosis, particularly in cases presenting with atypical clinical appearance. This study aims to present the process of developing targeted multiplex PCR and evaluate its application in infectious uveitis diagnosis.   Methods: This was a cross-sectional study to evaluate the diagnostic performance of targeted multiplex PCR in infectious uveitis. We obtained ocular fluid samples and reviewed medical records of uveitis patients who underwent ocular fluid analysis at Cipto Mangunkusumo Hospital from February 2022 to March 2023. PCR detection threshold values (DNA copies/mL) were 10.9 for Mycobacterium tuberculosis (Mtb), 672 for Epstein-Barr virus (EBV), 4.77 for Cytomegalovirus (CMV), 6.37 for Toxoplasma gondii (T. gondii), and 5.53 for Herpes simplex virus (HSV). With multiple pathogen selection, this method requires a lower volume of samples than single-plex PCR, as the latter will increase the sample volume linearly with each additional pathogen tested.   Discussion: Forty-seven aqueous or vitreous samples were analyzed. The positivity rate was 23.4% (11/47) with Mtb yielding the highest positivity (7/41; 17.1%). With final diagnosis as a reference, targeted multiplex PCR resulted in 32.3% (95% CI: 16.7 – 51.4%) sensitivity, 93.8% (95% CI: 69.8 – 99.8%) specificity, 90.9% (95% CI: 58.4 – 98.6%) positive predictive value, and 41.7% (95% CI: 35.2 – 48.4%) negative predictive value.   Conclusion: With its high specificity, targeted multiplex PCR is useful as a confirmatory but not screening tool in uveitis diagnosis. Ocular fluid analysis is an important part of the stepwise diagnostic approach in uveitis.